Perlindungan Hukum Terhadap Hak Cipta Geguritan Bali Di Indonesia - Dananjaya, Putu Bagus; Pramana, I Gede Pasek (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
Geguritan Bali as a Traditional Cultural Expression whose copyright is held by the State is a provision of Article 38 paragraph (1) of Law Number 28 Year 2014 concerning Copyright. Countries are required to inventory, preserve and preserve traditional cultural expressions. The problem is that the use of traditional cultural expressions is easily claimed to be the domain of other parties who registered and published it earlier. This study aims to analyze legal protection and legal remedies if the Bali Geguritan is reproduced without permission for commercial needs. This study uses a normative legal research method with a statutory approach. The results of this study indicate that the protection of Geguritan Bali's copyright works in the Copyright Act has not been able to protect the expression of traditional culture as a whole because of the blurring of norms and character differences between Intellectual Property Rights and Traditional Cultural Expressions. The Regional Government has the authority to file a lawsuit related to the multiplication of Geguritan Bali without permission for commercial needs. Based on the theory of the authority of the mandate granted by the state as the copyright holder to the Provincial Culture Office and the City Culture Office as the area carrying the Traditional Cultural Expressions.